Generics and Epistemic Injustice - Rosola, Martina (Ethical theory and moral practice, 2020)
In this paper, we argue that, although neglected so far, there is a strong link between generics and testimonial injustice. Testimonial injustice is a form of epistemic injustice that “occurs when prejudice causes a hearer to give a deflated level of credibility to a speaker’s word” (Fricker 2007: 1). Generics are sentences that express generalizations about a category or about its members without specifying what proportion of the category members possess the predicated property. We argue that generics are especially suited to cause testimonial injustice for three reasons. First, generics elicit an “inferential asymmetry” (Cimpian et al. Cogn Sci 34(8):1452-1482, 2010). That is, generics are accepted even if only a few individuals possess the predicated property but are, nonetheless, taken to refer to almost all the members of the category. This peculiar combination makes generics particularly apt to cause testimonial injustice. High resistance to counter-evidence is a crucial feature of prejudice, the cause of testimonial injustice, and the more highly predictive a generalization the more it will be employed in concrete situations, leading to instances of testimonial injustice. Second, generics seem to play a key role in leading people to develop essentialist beliefs (Gelman et al. Cogn Psychol 61(3): 273-301, 2010; Rhodes et al. Proc Natl Acad Sci 109(34): 13526-13531, 2012). Subjects holding such beliefs treat categories as warranting strong generaliations over their members. Therefore, they will be more likely to rely on prejudice while dealing with the category members. Finally, generics are outstandingly common in everyday speech. Hence, their noxious effects are amplified by their diffusion and should not be underestimated.